Can Metal Matrix‐Hydrophobic Nanoparticle Composites Enhance Water Condensation by Promoting the Dropwise Mode?. Issue 16 (28th August 2015) - Damle, Viraj G.; Sun, Xiaoda; Rykaczewski, Konrad
Abstract : Incorporation of condensers treated with hydrophobic modifiers that promote the efficient dropwise condensation mode can significantly enhance the performance of power generation and desalination plants. However, this approach is not used in industry because of low thermal conductivity and limited durability of the thin hydrophobic coatings. Here, it is argued that metal matrix hydrophobic nanoparticle composites can be a robust and high thermal conductivity alternative to hydrophobic polymeric and ceramic thin films. By characterizing condensation on a wide range of mimicked composite surfaces, it is demonstrated that to promote dropwise condensation the filler nanoparticles must have size and spacing significantly smaller than the few micrometer average center‐to‐center separation distance between closest neighboring droplets prior to onset of the coalescence dominated growth stage. Furthermore, the nanoparticle density does not have to be high enough to make the surface hydrophobic, but only sufficiently high to reduce the contact angle hysteresis, and with that pinning of droplets during coalescence and gravity assisted shedding. Using experimental results in conjunction with condensation models, it is estimated that a substantial heat transfer enhancement can be achieved via promotion of sustained dropwise mode even by using copper and aluminum matrix composites fully loaded with polytetrafluoroethylene nanoparticles if the film thickness is below ≈0.5 mm. Abstract : Experimental measurements in conjunction with condensation models are used to demonstrate that metal matrix composites with hydrophobic nanoparticles, with sizes significantly smaller than the average separation distance between droplet nuclei, can provide a viable alternative for enhancing the total heat transfer rate during water condensation by promoting the dropwise mode.